2018
DOI: 10.1016/j.heliyon.2018.e00692
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and remediation of pollutants in Ghana's Kete-Krachi District Hospital effluents using granular and smooth activated carbon

Abstract: The need for simple, cheaper and high performance hospital effluent treatment system in Kete-Krachi District which is adjacent to the Lake Volta has necessitated this study. This study focuses on assessing, and treating Kete-Krachi District Hospital effluent using packed granular (GAC) and smooth activated carbon (SAC). The use of activated carbon is due to its less expensive method of operation, the ease to prepare from local raw materials, high availability, and effectiveness for treating hospital effluent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…( Hocquet et al, 2016 ; Khan et al, 2020 ; Majumder et al, 2021a ). Many studies have reported the presence of a high concentration of coliform species and other bacteria species from HWW in different countries across the world ( Table S1 ) ( Majumder et al, 2021a ; Tulashie et al, 2018 ; Vo et al, 2016 ). García-Muñoz et al (2017) reported the total coliform concentration of around 3.8 × 10 6 MPN/100 mL in HWW of Madrid, Spain ( García-Muñoz et al, 2017 ).…”
Section: Hospital Wastewatermentioning
confidence: 99%
“…( Hocquet et al, 2016 ; Khan et al, 2020 ; Majumder et al, 2021a ). Many studies have reported the presence of a high concentration of coliform species and other bacteria species from HWW in different countries across the world ( Table S1 ) ( Majumder et al, 2021a ; Tulashie et al, 2018 ; Vo et al, 2016 ). García-Muñoz et al (2017) reported the total coliform concentration of around 3.8 × 10 6 MPN/100 mL in HWW of Madrid, Spain ( García-Muñoz et al, 2017 ).…”
Section: Hospital Wastewatermentioning
confidence: 99%
“…Table 7 shows that the removal of pharmaceuticals from hospital wastewater has been investigated to a lesser extent, and this is because in many countries such wastewater is discharged into the sewers and treated together with municipal wastewater [ 8 ]. However, hospitals are considered to be a major source of pharmaceutical contamination, so treating them separately would be appropriate, as some pharmaceuticals may be present in high concentrations and would, therefore, be easier to treat [ 15 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tulashie et al (2018) also reported that hospital effluent treatment studies have been conducted using techniques such as membrane filtration, activated carbon adsorption, and advanced oxidation processes. However, these techniques were found to be expensive and difficult to operate, especially in hospitals established in developing countries seeking to treat these effluents [ 15 ]. In contrast, techniques based on biological methods can produce effluents that preserve water quality standards at a reasonable cost for these facilities [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…al, and Chung photocatalytically degraded V5R using Fe-Doped Titania [ 19 ], and TiO2 catalysts [ 13 ], nonetheless, this method can potentially produce intermediate products which may be more lethal than the pristine V5R [ 12 , 13 ]. Adsorption with activated carbon is one of the cost-effective, sludge-free, and simple to operate wastewater treatment processes [ 20 , 21 , 22 ]. Thus, the elimination of dyes from wastewater by activated carbon is becoming popular because of its adsorptive efficiency for a wider range of adsorbates [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%